Google Site-Based Interactive Electronic Module as Basic Writing Media - Jusriati, Jusriati; Kurniadi, Wisnu; Azizah, Andi; Nawawi, Nurhidayah (Universitas Cokroaminoto Palopo, 2023)
This research aims to develop electronic module-based Google Site for learning basic writing in the English Language Education study program at Muhammadiyah University of Palopo. The results of the e-module that has been developed are then analyzed for its feasibility level through a validation process. This research uses Research & Development with the ADDIE development model which focuses on four stages, namely define, design, develop and disseminate. The results of this research reveal that the module that has been developed can be categorized as very feasible after carrying out a validation process by the validators in terms of media and material. Furthermore, after all aspects of both media and material in this research were declared very feasible, it can be concluded that the product can be tested on a small scale with students. In this small-scale test students are asked to access the e-module application and are then asked to use it. After that students are then asked to provide responses related to the use of the e-module. The questionnaire focuses on linguistic aspects, presentation of material, usefulness and graphics. There were 20 students involved in this small-scale testing and the results were 81%, so it can be concluded that these students claimed that the e-module that had been developed was very good.